Role Of Fintech In Green Finance And Sustainable Development - Ghosh, Krishnendu (Gyan Management Journal, 2020)
Sustainable  development  is  the  common  goal  of  human  landscape.  The  evolution  to sustainable  economy is an inevitable trend of economic development. FinTech and green finance is strong driving  force for sustainable economic development. This article aims to discuss the significant interactions  among FinTech, green finance and sustainable development. This paper outlines the broad areas for  the possible application of FinTech to green finance and sustainable development. The methodology  used for the article is mainly the theoretical framework build based on the existing literature. This  study  could benefit policymakers and  researchers in understanding the implications big data and  blockchain  and  draws  preliminary  recommendations  for  policy  makers  interested  in  connecting  FinTech,  big  data  and  blockchain  with  green  finance  and  sustainable  development.  The  study  concludes that FinTech plays a vital role in green finance and sustainable development.
Keywords: Sustainable development; FinTech; green finance; big data; blockchain